Novel distribution of the secretory leucocyte proteinase inhibitor in kidney - Sophie Ohlsson; Irena Ljungkrantz; Kjell Ohlsson; Mårten Segelmark; Jörgen Wieslander (Mediators of Inflammation)
The secretory leucocyte proteinase inhibitor (SLPI) is a low molecular weight, tissue-specific inhibitor of, for example, elastase and cathepsin G, which also have antimicrobial capacity. SLPI has been localised to the respiratory, gastrointestinal and genital tracts, but so far not to the kidney. The presence of SLPI in renal tubuli cells was demonstrated using immunohistochemistry and, by means of in situ hybridisation on human renal biopsies, we were able to demonstrate SLPI production. In various inflammatory conditions in the kidneys, the protease-antiprotease balance is disturbed. For this reason, as well as the possible role in the defence against ascending urinary tract infections, it is interesting to establish a source of SLPI in renal tubuli cells.